Sistem Pemberian Pembiayaan Kendaraan Bermotor Pada Pt. Bpr Syariah Artha Madani Kantor Cabang Pembantu Syariah, Cikarang - Ali Mutaufiq (Jurnal Manajemen Bisnis dan Keuangan, 2020)
This study aims to determine "Motor Vehicle Financing System at PT. BPR Syariah Artha Madani Cikarang Sharia Sub-Branch Office". The method used in this research is descriptive research. This research focuses on: 1. Motor Vehicle Financing procedure with Murabahah contract at Bank Artha Madani KCPS Cikarang. 2. Requirements in applying for Motor Vehicle Financing at Bank Artha Madani KCPS Cikarang